Chlorin e6: A Promising Photosensitizer in Photo-Based Cancer Nanomedicine - Hak, Arshadul; Ali, Mohammad Sadik; Sankaranarayanan, Sri Amruthaa; Shinde, Vinod Ravasaheb; Rengan, Aravind Kumar (ACS applied bio materials, 2023)
Conventional cancer treatment modalities are often associated with major therapeutic limitations and severe side effects. Photodynamic therapy is a localized noninvasive mode of treatment that has given a different direction to cancer research due to its effectivity against a wide range of cancers and minimal side effects. A photosensitizer is the key component of photodynamic therapy (PDT) that generates cytotoxic reactive oxygen species to eradicate cancer cells. As the therapeutic effectivity of PDT greatly depends upon the photosensitizer, great efforts have been made to search for an ideal photosensitizer. Chlorin e6 is a FDA approved second generation photosensitizer that meets the desired clinical properties for PDT. It is known for its high reactive oxygen species (ROS) generation ability and anticancer potency against many types of cancer. Hydrophobicity is a major drawback of Ce6 that leads to its poor biodistribution and rapid clearance from the circulatory system. To overcome this drawback, researchers have designed and fabricated several types of nanosystems, which can enhance Ce6 solubility and thereby enhance its bioavailability. These nanosystems also improve tumor accumulation of Ce6 by selectively targeting the cancer cells through passive and active targeting. In addition, Ce6 has been employed in many combination therapies like chemo-photodynamic therapy, photoimmunotherapy, and combined photodynamic–photothermal therapy. A combination therapy is more curative than a single therapy due to the synergistic effects of individual therapies. Ce6-based nanosystems for combination therapies have shown excellent results in various studies and provide a promising platform for cancer treatment.